- #1

- 27

- 0

36(2x-y)^2-25(u-2y)^2

i was thinking to expand the brackets first?? but im not really sure

- Thread starter dcgirl16
- Start date

- #1

- 27

- 0

36(2x-y)^2-25(u-2y)^2

i was thinking to expand the brackets first?? but im not really sure

- #2

mathman

Science Advisor

- 7,891

- 460

a^2-b^2=(a+b)(a-b)

- #3

- 27

- 0

alright so once i've got that what do i do with the 25 and 36 outside the brackets

- #4

matt grime

Science Advisor

Homework Helper

- 9,395

- 3

Once you 'do that' you don't have any 25 or 36 outside any brackets.

- #5

- 184

- 0

5^2 = 25

6^2 = 36

6^2 = 36

- #6

Gib Z

Homework Helper

- 3,346

- 5

Let 2x-y=A and u=2y=B

36(A^2) - 25(B^2)= (6A)^2 - (5B)^2

36(A^2) - 25(B^2)= (6A)^2 - (5B)^2

- #7

- 612

- 1

- Last Post

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 17

- Views
- 4K

- Replies
- 5

- Views
- 2K

- Replies
- 6

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 1K

- Replies
- 6

- Views
- 1K

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 2K

- Replies
- 1

- Views
- 10K

- Replies
- 10

- Views
- 2K